SP innovation ‘pires’ (pathways) in Mozambique: A historical and gendered perspective - Forsythe, Lora; Chipenembe, Maria Judite; Madroba, Gonzaga Luis; Lamboll, Richard; Mulwa, Chalmers K. (University of Greenwich, 2023)
Throughout history, the movement of people has brought with it the movement of food crops. These movements and the re-embedding of both food crops and populations in new and nonindigenous contexts are sites that reveal dynamic social relations profoundly linked to colonial histories, patriarchal power hierarchies and neoliberal ideology. This research paper and the accompanying visual representations explore this theme through an analysis of community discussions that bring a historical perspective to the non-indigenous crop of sweetpotato in Manica and Nampula provinces of Mozambique. The study involved qualitative, codesigned and participatory research that involved an interdisciplinary team from Mozambique, Kenya and the UK working with community elders, and male and female farmers. Findings from the study reveal layers of historic ‘encounters’ with external actors anchored around sweetpotato, from colonial powers to the private companies, international donors, agricultural extension and crop breeding institutions. These encounters are united in their reflection of patriarchal and colonial/ postcolonial power dynamics that have shaped how men and women farm overtime, and the results and the reverberations that follow. Communities, particularly older women, have developed strategies to maintain ‘traditional’ farming, food cultures and valued varieties, in the context of increasing pressure from climate and environmental change, conflict and the private sector. Important context and lessons can be drawn from research that uses a historical and gender perspective in understanding innovation pathways. It can inform a deeper understanding of trait preferences and broader, diverse, interactions with released crop varieties, which are relevant to crop-breeding communities.